Introduction to classical mechanics : - Morin, David (Cambridge University Press, 2008)
Brand NEW, International Edition. ISBN and Cover same with similar contents as US edition. Printed in Black & White. End Chapter Exercises may differ. No CD/Access code. Legal to use despite any disclaimer. We also ship to PO Box addresses. Printed in English. We may ship the books from multiple warehouses across the globe, including India depending upon the availability of inventory storage. In case of orders from Europe, custom charges may comply by the relevant government authority and we are not liable for it.100% Customer satisfaction guaranteed! Please feel free to contact us for any queries. Customer Satisfaction Guaranteed.